The microbiology of central nervous system infections - Kon, Kateryna Volodymyrivna; Rai, Mahendra (Clinical microbiology diagnosis, treatment and prophylaxis of infections, 2018)
The Microbiology of Central Nervous System Infections, Volume 3, discusses modern approaches to the diagnosis, treatment and prophylaxis of central nervous system (CNS) infections. This new release is divided into five sections that cover treatment strategies, imaging, molecular diagnosis, management of CNS infections with metal nanoparticles, and prophylaxis of CNS infections, including bacterial, viral and fungal infections. The last section contains a chapter on transmissible spongiform encephalopathies and modern trends in its diagnosis and treatment. University teachers, medical practitioners, graduate and postgraduate students, researchers in microbiology, and those in the pharmaceutical and laboratory diagnostic industries will find the book very important.